Achieving Sustainability in Banking through Smart Product-Service Systems: An Integrated Robust Fuzzy DEMATEL - Hu, Ya-Ping; Lin, Chun-Wei; Hariyadi, Eko (International Journal of Economics and Financial Issues, 2024)
This article explores the integration of the Triple Bottom Line concept in Smart Product Service Systems (S-PSS) within the banking industry. It emphasizes the importance of balancing economic, social, and environmental factors for sustainable development. By implementing personalized solutions and environmentally friendly practices, banks can strengthen customer relationships, drive loyalty, and reduce their ecological footprint. The study also highlights the benefits of effective information interaction and the potential for new financial services that prioritize economic value, societal well-being, and environmental conservation. Overall, the document provides a comprehensive framework for sustainable business practices in the banking sector.